See how they run : campaign dreams, election schemes, and the race to the White House - Goodman, Susan E., 1952- (Bloomsbury, 2008)
Provides a short history of Democracy, explains the process by which presidential campaigns are conducted, and discusses why citizens should exercise their right to vote.